UMP, TT Vision Technology Sdn. Bhd. Collaborate in Engineering and Technology - Radhiyah, Abd Aziz; Nadira Hana, Abdul Hamid (2022)
BAYAN LEPAS, 2 June 2022 - Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with TT Vision Technology Sdn. Bhd. in strengthening university-industry strategic collaboration.